Cold Nuclear Matter Effects on Isolated Prompt Photon and Isolated Prompt Photon＋Jet Productions in Relativistic Heavy-Ion Collisions - 代巍 陈时勇 张本威 王思科 (Communications in theoretical physics, 2013)
We investigate the cold nuclear matter （CNM） effects on isolated prompt photon and isolated prompt photon associated jet productions in nuclear collisions at the NLO accuracy by using the EPS09 NLO nuclear parton distribution functions and their error sets. Nuclear modification factors of isolated prompt photon and isolated prompt photon＋jet productions due to CNM effects in p＋A and A＋A reactions at the RHIC and the LHC are provided with varying rapidity and transverse momentum of the final state photon. It is shown that the CNM effects on isolated prompt photon and photon＋jet are modest, which give a small enhancement at low PT region and a more obvious suppression at large pT at central rapidity. At forward rapidity a pronounced suppression of γ as well as γ＋jet is always observed.